Platinum-group element systematics in the North Atlantic Igneous Province: New insights from Northern Irish and Irish magmatism - Anna O. Morrison; Michael J. Stock; Mark R. Cooper; Jens C.Ø. Andersen; Hannah S.R. Hughes; Elliot J. Carter; Jack Beckwith; Iain McDonald; Andrew C. Kerr; Paul Mohr (Lithos, 2026)

Climate Attribution in Fishery Stock Assessment: Case Studies From the Northeast U.S. Groundfish Stocks - Lisa A. Kerr; Jamie T. Behan; Steven X. Cadrin; Alexander C. Hansell; Amanda R. Hart; Jessica A. Kittel; Scott I. Large; Timothy J. Miller; Abigail S. Tyrell (Fish and Fisheries, 2026)
Climate change poses an unprecedented risk to fisheries ecosystems and economies globally. Ocean warming has led to observed geographic shifts and changes in the productivity of fish stocks. Due to the rapid pace of change in many of the world's oceans, there is a critical need to develop and apply scientific knowledge and tools that can help account for non‐stationarity and integrate climate and ecosystem drivers into fishery stock assessment to improve management outcomes. We developed a structured approach to identify and integrate the impact of climate and ecosystem change on fish stock dynamics in the context of stock assessment processes. We describe lessons learned in the application of this approach to groundfish stock assessment processes in the Northeast U.S. (American plaice, Atlantic cod and yellowtail flounder). The approach involves three general steps: (1) synthesizing the state of knowledge on stock‐climate relationships, (2) accounting for climate impacts on key data inputs and biological parameters that inform assessments, and (3) developing and evaluating the performance of climate informed stock assessment models. This approach represents an advance in climate attribution within stock assessment and is expected to enhance assessment performance and projection realism, supporting fisheries decision‐making for future resource sustainability.

The contributions of Frederick Hardy to tropical soil science and soil survey - R. Wayne Borden; Stephen H. Hallett; Brian Kerr (CATENA, 2026)

Multimorbidity as a predictor of mortality in companion dogs - Eric R. Foreman; Laura Corlin; Kate E. Creevy; Jessica M. Hoffman; Joshua M. Akey; Rozalyn M. Anderson; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Matthew D. Dunbar; Virginia R. Fajt; Erica C Jonlin; et al. (GeroScience, 2026)

Reevaluating introduced herbivores in conservation - Jonas Trepel; Robert Buitenwerf; Kristy Ferraro; Elizabeth le Roux; Erick Lundgren; Brian Maitner; Tanya Strydom; Jens‐Christian Svenning; Matthew R. Kerr (Conservation Biology, 2026)

Expression of the P2X1 receptor remains in the type II spiral ganglion neurons in the mature rat cochlea - Prakansha N. Kumar; Srdjan M. Vlajkovic; Peter R. Thorne; Haruna Suzuki-Kerr (Purinergic Signalling, 2026)
Our sense of hearing commences in the cochlea, the peripheral sensory organ for hearing. Spiral ganglion neurons (SGN) in the cochlea are primary auditory neurons responsible for auditory neurotransmission. There are two classes of SGNs: type I SGNs, which make up 90-95% of the SGN population, and type II SGNs, which make up the remainder. Previous studies have shown that SGNs express a combination of purinergic (P2X, P2Y and adenosine) receptors at the mRNA and protein levels. In this study, we have focused on the P2X1 receptor to characterise its expression pattern in the Wistar rat cochlea at postnatal day 8 and in adult (6–8-week-old) rats of both genders using immunohistochemistry. Our results show differential expression of P2X1 receptors in 9.4-14.2% of SGNs in the adult cochlea, and 14.2-23.3% in the cochlea of P8 pups. In most of these neurons, P2X1 receptors were co-expressed with peripherin-1, an established type II SGN marker. These results suggest a potential role for the P2X1 receptor as a modulator of auditory neurotransmission in type II spiral ganglion neurons.

Higher burden of neuropsychiatric symptom-like behaviors associated with canine cognitive dysfunction compared to normal aging in the Dog Aging Project - Daniel W. Fisher; Jillian R. Fisher; Silvan R. Urfer; NhiVan A. Tran; Kathleen F. Kerr; Martin Darvas (GeroScience, 2026)

Skeletal muscle atrophy induced by aging and disuse atrophy are strongly associated with the upregulation of the endoplasmic stress protein CHOP in rats - J. Max Michel; Joshua S. Godwin; Nathan R. Kerr; Thomas E. Childs; Frank W. Booth; C. Brooks Mobley; David C. Hughes; Michael D. Roberts (Molecular Biology Reports, 2025)
Background While canonical anabolic and proteolytic pathways have been well examined in the context of skeletal muscle proteostasis, the roles of endoplasmic reticulum stress (ERS) and the induced unfolded protein response (UPR) are underappreciated. Thus, we aimed to determine whether aging and/or disuse atrophy in rats altered skeletal muscle ERS/UPR markers. Methods and Results Soleus (SOL) and plantaris (PLT) muscles of 3-month-old (mo), 6 mo, 12 mo, 18 mo, and 24 mo rats (9–10 per group, 48 in total) were analyzed for UPR proteins with further analysis performed on the protein CHOP. The gastrocnemius muscles of 4 mo rats that had undergone hindlimb immobilization (HLI, n = 12) or sham casting (CTL, n = 12) were analyzed for similar targets as well as more extensive CHOP-related targets. CHOP protein was greater in the PLT and SOL of 18 and 24 mo rats versus other age groups ( P < 0.05). Moreover, negative correlations existed between CHOP expression and normalized PLT ( R =-0.702, P < 0.001) and SOL ( R =-0.658, P < 0.001) muscle weights in all rats analyzed at different ages. CHOP protein expression was also greater in the gastrocnemius of HLI versus CTL rats ( P < 0.001), and a negative correlation existed between CHOP protein expression and normalized muscle weights in these rats ( R =-0.814, P < 0.001). Nuclear CHOP protein levels ( P < 0.010) and genes transcriptionally regulated by CHOP were also greater in HLI versus CTL rats ( P < 0.001) implicating transcriptional activity of CHOP is elevated during disuse atrophy. Conclusions CHOP is operative during aging- and disuse-induced skeletal muscle atrophy in rodents, and more research is needed to determine if CHOP is a key mechanistic driver of these processes.

Subcellular localization of the P2X4 receptor in sensory hair cells of Wistar rat cochlea - Ziyin Huang; Jacqueline M. Ross; Shelly C. Y. Lin; Prakansha N. Kumar; Kevin Roy; Srdjan M. Vlajkovic; Peter R. Thorne; Haruna Suzuki-Kerr (Histochemistry and Cell Biology, 2025)
Our sense of hearing starts in the inner ear organ, the cochlea, which contains two types of auditory hair cells for signal transduction. Earlier research showed that the complex cochlear physiology is regulated in part by purinergic signalling through activation of purine-mediated P2X, P2Y and adenosine receptors expressed in the cochlea. This study aims to extend our knowledge of purinergic signalling in the cochlea by comprehensively characterising the expression of the P2X4 receptor subtype. Wistar rat cochlea (embryonic day 20.5–6 weeks, both sexes) were collected, and the P2X4 expression was examined by immunohistochemistry. Robust P2X4 expression was found in the organ of Corti (OoC) in the inner hair cells (IHCs) and outer hair cells (OHCs), confirmed by double-labelling with hair cells (HCs) marker myosin VIIa. In IHCs, a robust cytoplasmic P2X4 expression occurred throughout the cell body, with the most intense signal at the medial side. In OHCs, P2X4 formed puncta near the apical and basal ends of the cell body. Using markers for subcellular organelles, P2X4 immunoreactivity was predominately associated with the trans-Golgi network apparatus and early endosomes in IHC and with early endosomes and lysosomes in OHC in the mature cochlea. In both cell types, some co-localisation of P2X4 with presynaptic marker was also observed. Taken together, these observations suggest unique roles for P2X4 in mature IHCs and OHCs as a purinergic receptor subtype responsible for the homeostatic regulation of hair cells and auditory sensory transduction.

Apicomplexan and non-metazoan microeukaryotes in the thermosensitive reef-building coral Acropora hyacinthus shift in abundance throughout an extreme coral bleaching event - Athena Peterson; Sunni Patton; Emily R. Schmeltzer; Carsten G. B. Grupstra; Lauren I. Howe-Kerr; J. Grace Klinges; Rebecca L. Maher; Adriana Messyasz; Sarah Seabrook; Andrew R. Thurber; Adrienne M. S. Correa; Rebecca L. Vega Thurber (Frontiers in Marine Science, 2025)
Coral reefs play vital roles in global marine systems and are currently facing increased threats of bleaching. Coral bleaching is heavily influenced by the host-associated microeukaryote community – most notably the dinoflagellate family Symbiodiniaceae. The apicomplexan family Corallicolidae, is the second most abundant member of the microeukaryote community, yet their role in coral health is largely unknown. To explore the role that this apicomplexan and the greater non-metazoan microeukaryotic community play in coral health, samples of a thermally sensitive scleractinian coral, Acropora hyacinthus , were collected over the course of a severe coral bleaching event and its aftermath. Through 18S rRNA gene sequencing analysis, we found that taxa within the family Corallicolidae were relatively enriched in corals during, and immediately after, the severe bleaching event as compared to before or one year after. Although utilizing 18S rRNA gene sequencing methods is not the standard for Symbiodiniaceae community profiling, we were able to observe symbiont shuffling among the Symbiodiniaceae communities, as the dominant algal symbiont shifted from the genus Cladocopium to the genus Symbiodinium following the bleaching event. Furthermore, the non-metazoan microeukaryote community displayed a general shift towards a state of dysbiosis; evidenced by substantial changes in both microeukaryote community composition and dispersion. These results offer insight into the dynamics of apicomplexans throughout the course of an increasingly common global coral reef stressor.

Albinism research in a Southern African setting: unique findings - Jennifer G. R. Kromberg; Robyn A. Kerr (Journal of Community Genetics, 2025)
Research on oculocutaneous albinism (OCA) in the black African population has been ongoing for 52 years (1971–2023) in the Division of Human Genetics, University of the Witwatersrand, Johannesburg, South Africa. The aim of the present study was to review all the relevant published articles and focus on selected articles with unique findings. The results showed that unique findings were reported in psychosocial, cultural, epidemiological, clinical and molecular fields of study. The local prevalence of albinism was found to be 1 in 3900, higher than that reported in many other countries, although a worldwide review on prevalence showed that only 26/193 (13%) countries had published figures; the commonest types of OCA found were OCA2 and then OCA3; the high rate of skin cancer was documented; and the natural history of OCA described. Molecular studies showed that the 2.7 kb deletion mutation in the OCA2 gene is the common mutation in OCA2 locally, and further identified unique mutations in TYRP1 causing rufous albinism (OCA3) in this population. An early study found that after the birth of a child with OCA maternal-infant bonding was delayed, and only established some months later. Further research revealed that superstitions and myths surrounded the birth and the death of a person with OCA, and the belief that powerful medicines could be made from body parts, was very disturbing. Genetic causes of OCA were poorly understood by affected individuals, their relatives and communities, and genetic counselling is essential. In summary, over 30 studies were undertaken and published over a period of five decades, and many presented unique findings on this under-researched inherited condition.

Rationale and design of the Dog Aging Project precision cohort: a multi-omic resource for longitudinal research in geroscience - Jena Prescott; Amber J. Keyser; Paul Litwin; Matthew D. Dunbar; Robyn McClelland; Audrey Ruple; Holley Ernst; Brianna L. Butler; Mandy Kauffman; Anne Avery; Benjamin R. Harrison; Maria Partida-Aguilar; et al. (GeroScience, 2025)

Increased BMI is associated with an altered decision-making process during healthy food choices in males and females - Larenas G; Luarte L; Kerr B; Ossandón T; Cortés V; Baudrand R; Pérez Leighton C (Appetite, 2025)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

5-HT2C agonism as a neurotherapeutic for sarcopenia: preclinical proof of concept - Nathan R. Kerr; Anna R. Dashtmian; Fereshteh B. Darvishi; Charles D. Brennan; Sindhuja N. Ayyagari; Peter J. Moore; Jose A. Viteri; Meifang Wang; Mark M. Rich; Brian C. Clark; W. David Arnold (GeroScience, 2025)

Advancements in Riverine Fish Movement Modeling: Bridging Environmental Complexity and Fish Behavior - D. P. Zielinski; J. Kerr; K. M. Bærum; O. M. Simmons; A. T. Silva; R. A. Goodwin (Reviews in Fisheries Science & Aquaculture, 2025)

Assessing the effect of multispecies interactions on precautionary reference points using an ensemble modelling approach: A North Sea case study - Michael A. Spence; James A. Martindale; Khatija Alliji; Hayley J. Bannister; Robert B. Thorpe; Nicola D. Walker; Peter J. Mitchell; Matthew R. Kerr; Paul J. Dolder (Fisheries Research, 2024)

Drought-related mortality, growth and non-structural carbohydrate dynamics in two conifer species during early stages of development - David R. Woodruff; Frederick C. Meinzer; Katherine A. McCulloh; Kimberly O’Keefe; Kelly L. Kerr; Danielle E. M. Ulrich; Johnathan G. Crandall (Trees, 2024)

Characterizing dog cognitive aging using spontaneous problem-solving measures: development of a battery of tests from the Dog Aging Project - Stephanie H. Hargrave; Emily E. Bray; Stephanie McGrath; Gene E. Alexander; Theadora A. Block; Naomi Chao; Martin Darvas; Laura E. L. C. Douglas; Janet Galante; Brenda S. Kennedy; Breonna Kusick; Julie A. Moreno; et al. (GeroScience, 2024)

The companion dog as a model for inflammaging: a cross-sectional pilot study - Sarah M. Schmid; Jessica M. Hoffman; Jena Prescott; Holley Ernst; Daniel E. L. Promislow; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; et al. (GeroScience, 2024)

A biogeographic–macroecological perspective on the rising novelty of the biosphere in the Anthropocene - Matthew R. Kerr; Alejandro Ordonez; Felix Riede; Jens‐Christian Svenning (Journal of Biogeography, 2024)
The concept of novel ecosystems has been discussed for over more than a decade to describe ecosystems that have an altered species composition and function, such that the community has crossed a threshold forbidding a return to its historical state. While spatial and temporal community compositional change has been well studied in biogeography, studies on novel ecosystems in a modern context are few and tend towards classifying novelty based on a static baseline. Given that the abiotic and biotic drivers of novelty are in a state of rapid change, and reaching levels unprecedented within the last hundred thousand to million years, defining such a threshold requires additional thought. Here, we discuss a biogeographical–macroecological perspective on novel ecosystems, exploring how such a threshold for novelty can be defined in an environment undergoing progressive global change and suggesting pathways through which the emergence and spread of novelty can be further explored, understood and managed.

Diet Affects Egg Laying, Biomass, and Stable Isotope Values in Tetragnathid Spiders - Sarah Kerr; Ryan R. Otter (Bulletin of Environmental Contamination and Toxicology, 2024)

Observing Antarctic Bottom Water in the Southern Ocean - Alessandro Silvano; Sarah Purkey; Arnold L. Gordon; Pasquale Castagno; Andrew L. Stewart; Stephen R. Rintoul; Annie Foppert; Kathryn L. Gunn; Laura Herraiz-Borreguero; Shigeru Aoki; Yoshihiro Nakayama; Alberto C. Naveira Garabato; et al. (Frontiers in Marine Science, 2023)
Dense, cold waters formed on Antarctic continental shelves descend along the Antarctic continental margin, where they mix with other Southern Ocean waters to form Antarctic Bottom Water (AABW). AABW then spreads into the deepest parts of all major ocean basins, isolating heat and carbon from the atmosphere for centuries. Despite AABW’s key role in regulating Earth’s climate on long time scales and in recording Southern Ocean conditions, AABW remains poorly observed. This lack of observational data is mostly due to two factors. First, AABW originates on the Antarctic continental shelf and slope where in situ measurements are limited and ocean observations by satellites are hampered by persistent sea ice cover and long periods of darkness in winter. Second, north of the Antarctic continental slope, AABW is found below approximately 2 km depth, where in situ observations are also scarce and satellites cannot provide direct measurements. Here, we review progress made during the past decades in observing AABW. We describe 1) long-term monitoring obtained by moorings, by ship-based surveys, and beneath ice shelves through bore holes; 2) the recent development of autonomous observing tools in coastal Antarctic and deep ocean systems; and 3) alternative approaches including data assimilation models and satellite-derived proxies. The variety of approaches is beginning to transform our understanding of AABW, including its formation processes, temporal variability, and contribution to the lower limb of the global ocean meridional overturning circulation. In particular, these observations highlight the key role played by winds, sea ice, and the Antarctic Ice Sheet in AABW-related processes. We conclude by discussing future avenues for observing and understanding AABW, impressing the need for a sustained and coordinated observing system.

Soil Moisture and Sea Surface Salinity Derived from Satellite-Borne Sensors - J. Boutin; S. Yueh; R. Bindlish; S. Chan; D. Entekhabi; Y. Kerr; N. Kolodziejczyk; T. Lee; N. Reul; M. Zribi (Surveys in Geophysics, 2023)
The monitoring of soil moisture and sea surface salinity over the Earth has been profoundly enhanced during the last thirteen years due to a new generation of satellite sensors. L-band radiometry is currently the only technology providing direct measurements of soil moisture, insensitive to surface roughness and distribution of elements in the soil, and the only technology the only technology for measuring that allows us to measure sea surface salinity from space. The Soil Moisture and Ocean Salinity (SMOS) and Soil Moisture Active Passive (SMAP) satellite missions resolve global and local variability with a spatial resolution of approximately 43 km, a swath width close to 1000 km, and a sampling time, for each mission, of at least twice every 3 days. These resolutions and samplings can be increased by either merging data from the two sensors, and with complementary information gathered from other passive or active sensors, or with in situ information at higher spatial resolution. Numerous scientific studies based on the use of this new type of measurement have led to a better understanding and constraint of the processes governing the variability of the water cycle, ocean circulation and the Earth's climate. The continuity of measurements, and the increased spatial and radiometric resolution is critical for fulfilling scientific needs. Future L-band radiometry missions currently being planned in Europe (the Copernicus Imaging Microwave Radiometer), and in China (the Ocean Salinity mission) should provide better constraints on auxiliary parameters by combining multiple frequencies, but they will not have improved spatial resolution beyond SMOS and SMAP. The temporal continuity with SMOS and SMAP will likely not be ensured. In parallel, new concepts are being developed to increase spatial resolution of both land and ocean parameters.

Creating conservation strategies with value‐focused thinking - David M. Martin; Joshua G. Goldstein; David R. Smith; Jessica Musengezi; Jessie G. Rountree; G. A. Pabodha Galgamuwa; Aileen Craig; Michelle Dietz; Caitlin Kerr (Conservation Biology, 2023)
Biodiversity and human well‐being strategies are only as good as the set of ideas people think about. We evaluated value‐focused thinking (VFT), a framework that emphasizes creating objectives and strategies that are responsive to the objectives. We performed a proof‐of‐concept study of VFT with 6 conservation planning teams at a global conservation organization. We developed a package of materials related to VFT, including meeting–session agendas, a virtual facilitation template, facilitator's guide, and evaluation questionnaires. We used these materials to test whether VFT applied in a group setting resulted in high‐quality conservation strategies and participant satisfaction and whether our materials were scalable, meaning that someone newly trained in VFT could facilitate planning meetings that resulted in high‐quality strategies and participant satisfaction, as compared with an experienced VFT facilitator. Net response indicated positive compelling, feasible, creative, and representative ratings for the conservation strategies per team. Participants indicated satisfaction overall, although satisfaction was greater for objectives than for strategies. Among the participants with previous conservation planning experience, all were at least as satisfied with their VFT strategies compared with previously developed strategies, and none were less satisfied ( p = 0.001). Changes in participant satisfaction were not related to facilitator type (experienced or inexperienced with VFT) ( p > 0.10). Some participants had a preconceived sense of shared understanding of important values and interests before participating in the study, which VFT strengthened. Our results highlight the advantages of structuring the development and evaluation of conservation planning frameworks around VFT.

Physical-biological drivers modulating phytoplankton seasonal succession along the Northern Antarctic Peninsula - Raul Rodrigo Costa; Afonso Ferreira; Márcio S. de Souza; Virginia M. Tavano; Rodrigo Kerr; Eduardo R. Secchi; Vanda Brotas; Tiago S. Dotto; Ana C. Brito; Carlos Rafael B. Mendes (Environmental Research, 2023)

Consumer feces impact coral health in guild-specific ways - Carsten G. B. Grupstra; Lauren I. Howe-Kerr; Jesse A. van der Meulen; Alex J. Veglia; Samantha R. Coy; Adrienne M. S. Correa (Frontiers in Marine Science, 2023)
Animal waste products are an important component of nutrient cycles and result in the trophic transmission of diverse microorganisms. There is growing recognition that the feces of consumers, such as predators, may impact resource species, their prey, via physical effects and/or microbial activity. We tested the effect of feces from distinct fish trophic groups on coral health and used heat-killed fecal controls to tease apart physical versus microbial effects of contact with fecal material. Fresh grazer/detritivore fish feces caused lesions more frequently on corals, and lesions were 4.2-fold larger than those from sterilized grazer/detritivore feces; in contrast, fresh corallivore feces did not cause more frequent or larger lesions than sterilized corallivore feces. Thus, microbial activity in grazer/detritivore feces, but not corallivore feces, was harmful to corals. Characterization of bacterial diversity in feces of 10 reef fish species, ranging from obligate corallivores to grazer/detritivores, indicated that our experimental findings may be broadly generalizable to consumer guild, since feces of some obligate corallivores contained ~2-fold higher relative abundances of coral mutualist bacteria ( e.g., Endozoicomonadaceae), and lower abundances of the coral pathogen, Vibrio coralliilyticus , than feces of some grazer/detritivores. These findings recontextualize the ecological roles of consumers on coral reefs: although grazer/detritivores support coral reef health in various ways ( e.g. , promoting coral settlement and herbivory through the removal of detritus and sediments from the algal matrix), they also disperse coral pathogens. Corallivore predation can wound corals, yet their feces contain potentially beneficial coral-associated bacteria, supporting the hypothesized role of consumers, and corallivores in particular, in coral symbiont dispersal. Such consumer-mediated microbial dispersal as demonstrated here has broad implications for environmental management.

Associations between physical activity and cognitive dysfunction in older companion dogs: results from the Dog Aging Project - Emily E. Bray; David A. Raichlen; Kiersten K. Forsyth; Daniel E. L. Promislow; Gene E. Alexander; Evan L. MacLean; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; et al. (GeroScience, 2023)

Banking on a new understanding: translational opportunities from veterinary biobanks - D. LaLonde-Paul; L. Mouttham; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; Matthew D. Dunbar; Virginia R. Fajt; Annette L. Fitzpatrick; Unity Jeffery; et al. (GeroScience, 2023)

The developmental journey of therapies targeting purine receptors: from basic science to clinical trials - Seunga Han; Haruna Suzuki-Kerr; Srdjan M. Vlajkovic; Peter R. Thorne (Purinergic Signalling, 2022)
Since the discovery of ATP as an extracellular signalling molecule in 1972, purinergic signalling, mediated by extracellular purines and pyrimidines has been identified in virtually all mammalian tissues and is implicated in regulating fundamental cellular processes. In recent years, there has been an increasing focus on the pathophysiology and potential therapeutic interventions based on purinergic signalling. A vast range of compounds targeting purine receptors are in clinical development, and many more are in preclinical studies, which highlights the fast growth in this research field. As a tribute to Professor Geoffrey Burnstock’s legacy in purinergic signalling, we present here a brief review of compounds targeting purine receptors that are in different stages of clinical trials. The review highlights the 50-year journey from basic research on purinergic receptors to clinical applications of therapies targeting purine receptors.

Once-daily feeding is associated with better health in companion dogs: results from the Dog Aging Project - Emily E. Bray; Zihan Zheng; M. Katherine Tolbert; Brianah M. McCoy; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; Matthew D. Dunbar; et al. (GeroScience, 2022)

Feasibility and Effectiveness Assessment of Multi-Sectoral Climate Change Adaptation for Food Security and Nutrition - M. C. Tirado; J. L. Vivero-Pol; R. Bezner Kerr; K. Krishnamurthy (Current Climate Change Reports, 2022)
Purpose of Review This review aims to identify the evidence for the assessment of the effectiveness and feasibility of multi-sectoral climate adaptation for food security and malnutrition. This review and the assessments of the evidence inform the contents and confidence statements in section “multi-sectoral adaptation for malnutrition” and in the Executive Summary of the IPCC AR6 WGII Chapter 7: Health Wellbeing and Changing Community Structure. Recent Findings A review of adaptation for food security and nutrition FSN in West Africa concluded that food security and nutrition and climate adaptation are not independent goals, but often go under different sectors. Summary Most of the adaptation categories identified here are highly effective in reducing climate risks to food security and malnutrition, and the implementation is moderately or highly feasible. Categories include improved access to (1) sustainable, affordable, and healthy diets from climate-resilient, nutrition-sensitive agroecological food systems; (ii) health care (including child, maternal, and reproductive), nutrition services, water and sanitation; (iii) anticipatory actions, adoption of the IPC classification, EW-EA systems; and (iv) nutrition-sensitive adaptive social protection. Risk reduction, such as weather-related insurance, and risk management are moderately effective and feasible due to economic and institutional barriers. Women and girls’ empowerment, enhanced education, rights-based approaches, and peace building are highly relevant enablers for implementation of the adaptation options.

Closing the knowledge‐action gap in conservation with open science - Dominique G. Roche; Rose E. O'Dea; Kecia A. Kerr; Trina Rytwinski; Richard Schuster; Vivian M. Nguyen; Nathan Young; Joseph R. Bennett; Steven J. Cooke (Conservation Biology, 2022)
The knowledge‐action gap in conservation science and practice occurs when research outputs do not result in actions to protect or restore biodiversity. Among the diverse and complex reasons for this gap, three barriers are fundamental: knowledge is often unavailable to practitioners and challenging to interpret or difficult to use or both. Problems of availability, interpretability, and useability are solvable with open science practices. We considered the benefits and challenges of three open science practices for use by conservation scientists and practitioners. First, open access publishing makes the scientific literature available to all. Second, open materials (detailed methods, data, code, and software) increase the transparency and use of research findings. Third, open education resources allow conservation scientists and practitioners to acquire the skills needed to use research outputs. The long‐term adoption of open science practices would help researchers and practitioners achieve conservation goals more quickly and efficiently and reduce inequities in information sharing. However, short‐term costs for individual researchers (insufficient institutional incentives to engage in open science and knowledge mobilization) remain a challenge. We caution against a passive approach to sharing that simply involves making information available. We advocate a proactive stance toward transparency, communication, collaboration, and capacity building that involves seeking out and engaging with potential users to maximize the environmental and societal impact of conservation science.

Increased short interval intracortical inhibition in participants with previous hamstring strain injury - R. Buhmann; G. S. Trajano; G. K. Kerr; A. J. Shield (European Journal of Applied Physiology, 2022)

Preseason Cerebrovascular Function in Adolescent Athletes - Patricia R. Roby; Peter J. Duquette; Zachary Y. Kerr; Johna K. Register-Mihalik; Lee Stoner; Jason P. Mihalik (Annals of Biomedical Engineering, 2021)

Changes in Phytoplankton Communities Along the Northern Antarctic Peninsula: Causes, Impacts and Research Priorities - Afonso Ferreira; Raul R. Costa; Tiago S. Dotto; Rodrigo Kerr; Virginia M. Tavano; Ana C. Brito; Vanda Brotas; Eduardo R. Secchi; Carlos R. B. Mendes (Frontiers in Marine Science, 2020)

Changing Biogeochemistry of the Southern Ocean and Its Ecosystem Implications - Sian F. Henley; Emma L. Cavan; Sarah E. Fawcett; Rodrigo Kerr; Thiago Monteiro; Robert M. Sherrell; Andrew R. Bowie; Philip W. Boyd; David K. A. Barnes; Irene R. Schloss; Tanya Marshall; Raquel Flynn; et al. (Frontiers in Marine Science, 2020)

Widespread drought‐induced tree mortality at dry range edges indicates that climate stress exceeds species' compensating mechanisms - William R. L. Anderegg; Leander D. L. Anderegg; Kelly L. Kerr; Anna T. Trugman (Global Change Biology, 2019)
Drought‐induced tree mortality is projected to increase due to climate change, which will have manifold ecological and societal impacts including the potential to weaken or reverse the terrestrial carbon sink. Predictions of tree mortality remain limited, in large part because within‐species variations in ecophysiology due to plasticity or adaptation and ecosystem adjustments could buffer mortality in dry locations. Here, we conduct a meta‐analysis of 50 studies spanning >100 woody plant species globally to quantify how populations within species vary in vulnerability to drought mortality and whether functional traits or climate mediate mortality patterns. We find that mortality predominantly occurs in drier populations and this pattern is more pronounced in species with xylem that can tolerate highly negative water potentials, typically considered to be an adaptive trait for dry regions, and species that experience higher variability in water stress. Our results indicate that climate stress has exceeded physiological and ecosystem‐level tolerance or compensating mechanisms by triggering extensive mortality at dry range edges and provides a foundation for future mortality projections in empirical distribution and mechanistic vegetation models.

Staying cool: the importance of shade availability for tropical ectotherms - C.-C. Chou; D. M. Perez; S. Johns; R. Gardner; K. A. Kerr; M. L. Head; E. L. McCullough; P. R. Y. Backwell (Behavioral Ecology and Sociobiology, 2019)

Masking a fish's detection of environmental stimuli: application to improving downstream migration at river infrastructure - James R. Kerr; Paul S. Kemp (Journal of Fish Biology, 2019)
According to Signal Detection Theory, the ability to detect a stimulus (discriminability, d' ) is inversely related to the magnitude of internal and external noise. In this study, downstream moving brown trout Salmo trutta were used to investigate whether external hydrodynamic noise (in this case turbulence) could mask a signal that induced an unwanted response, such as rejecting accelerating velocity gradients commonly encountered at entrances to fish bypass channels. S. trutta behaviour was quantified in the absence (control) or presence of an accelerating velocity gradient created by an unconstricted or constricted channel, respectively, under two levels (low and high) of background turbulent kinetic energy (hydrodynamic noise). Experiments were conducted in an indoor recirculating flume in the dark and a range of passage metrics were quantified. Under the control condition, most ( ca . 91%) S. trutta passed, usually oriented downstream (67%), with minimal delay (median 0.13 min). In comparison, fewer S. trutta ( ca . 43%) passed under constricted conditions, they tended to orient facing into the flow ( ca . 64%) and delay was greater (median > 20 min). When viewed from a coarse‐scale perspective, discriminability of the velocity gradient was lower when turbulence was high suggesting masking of the signal occurred. However, the resulting increase in the percentage of fish that passed, decrease in time to pass and reduction in the distance at which S. trutta reacted (switched orientation) was subtle and non‐significant. Despite the mixed results obtained, the use of masking to manipulate an animal's perception of environmental stimuli as a fisheries management tool is conceptually valid and the results of this experiment present a useful stepping stone for future research.

High-resolution habitat and bathymetry maps for 65,000 sq. km of Earth’s remotest coral reefs - Sam J. Purkis; Arthur C. R. Gleason; Charlotte R. Purkis; Alexandra C. Dempsey; Philip G. Renaud; Mohamed Faisal; Steven Saul; Jeremy M. Kerr (Coral Reefs, 2019)

Evidence of intraspecific prey switching: stage-structured predation of polar bears on ringed seals - Jody R. Reimer; Hannah Brown; Elaine Beltaos-Kerr; Gerda de Vries (Oecologia, 2019)

Modeling marine pelagic fish species spatiotemporal distributions utilizing a maximum entropy approach - Lifei Wang; Lisa A. Kerr; Nicholas R. Record; Eric Bridger; Benjamin Tupper; Katherine E. Mills; Edward M. Armstrong; Andrew J. Pershing (Fisheries Oceanography, 2018)
Understanding how ocean conditions influence fish distributions is critical for elucidating the role of climate in ecosystem change and forecasting how fish may be distributed in the future. Traditional species distribution models are often applied to scientific‐survey data, which include species presence‐absence information, to predict distributions. Maximum entropy (MaxEnt) models are promising tools as they can be applied to presence‐only data (e.g., data collected from fishermen targeting a specific species or from observers in citizen‐science programs). We used MaxEnt models to relate occurrence records of three marine pelagic fish (Atlantic herring, Atlantic mackerel, and butterfish) in fishery‐dependent data to environmental conditions (sea surface temperature ( SST ) and chlorophyll‐ a concentration from satellite remote sensing, bathymetry, and climate indices), and evaluated model performance by both cross‐validation and validation using fishery‐independent data. We developed monthly habitat suitability maps for these fish in the Northwest Atlantic Shelf area, and assessed the relative influence of environmental factors on their distributions. Across months, their suitable habitat areas varied with each species exhibiting inshore‐offshore and north‐south movements in response to changing environmental conditions. Overall, SST and chlorophyll‐ a concentration had the greatest influence on the distributions of these fish, with bathymetry having moderate influence and climate indices having little influence. Our application of MaxEnt models enabled us to integrate presence‐only data and high resolution environmental data from satellite remote sensing to describe spatiotemporal distributions of marine pelagic fish. These models were used to hindcast species occurrence in relation to historical environmental conditions to evaluate their predictive performance, and have the potential to provide nowcasts in relation to current conditions or forecasts of species future distributions.

Climate change effects on wildland fire risk in the Northeastern and Great Lakes states predicted by a downscaled multi-model ensemble - Gaige Hunter Kerr; Arthur T. DeGaetano; Cathelijne R. Stoof; Daniel Ward (Theoretical and Applied Climatology, 2018)

K-complexes, spindles, and ERPs as impulse responses: unification via neural field theory - M. S. Zobaer; R. M. Anderson; C. C. Kerr; P. A. Robinson; K. K. H. Wong; A. L. D’Rozario (Biological Cybernetics, 2017)

A new eimerian (Apicomplexa: Eimeriidae), from ornate box turtle, Terrapene ornata (Agassiz) (Testudines: Emydidae) from northwest Arkansas, USA - Chris T. McAllister; Dagmara Motriuk-Smith; Catherine M. Kerr; Kristine N. Carmen; R. Scott Seville; Matthew B. Connior (Systematic Parasitology, 2017)

Effects of a 1-year randomised controlled trial of resistance training on blood lipid profile and chylomicron concentration in older men - Anthony P. James; Joanna Whiteford; Timothy R. Ackland; Satvinder S. Dhaliwal; Jenni J. Woodhouse; Richard L. Prince; Xingqiong Meng; Deborah A. Kerr (European Journal of Applied Physiology, 2016)

Subsurface Hydrology of the Lake Chad Basin from Convection Modelling and Observations - T. Lopez; R. Antoine; Y. Kerr; J. Darrozes; M. Rabinowicz; G. Ramillien; A. Cazenave; P. Genthon (Surveys in Geophysics, 2016)

The Western South Atlantic Ocean in a High-CO2 World: Current Measurement Capabilities and Perspectives - Rodrigo Kerr; Letícia C. da Cunha; Ruy K. P. Kikuchi; Paulo A. Horta; Rosane G. Ito; Marius N. Müller; Iole B. M. Orselli; Jannine M. Lencina-Avila; Manoela R. de Orte; Laura Sordo; Bárbara R. Pinheiro; Frédéric K. Bonou; et al. (Environmental Management, 2016)

Remote Sensing of Water Resources in Semi-Arid Mediterranean Areas: the joint international laboratory TREMA - L. Jarlan; S. Khabba; S. Er-Raki; M. Le Page; L. Hanich; Y. Fakir; O. Merlin; S. Mangiarotti; S. Gascoin; J. Ezzahar; M.H. Kharrou; B. Berjamy; et al. (International Journal of Remote Sensing, 2015)

Increasing Opportunistic Oral Cancer Screening Examinations: Findings from Focus Groups with General Dentists in Puerto Rico - Walter J. Psoter; Douglas E. Morse; Melba Sánchez-Ayendez; Carmen M. Vélez Vega; Maria L. Aguilar; Carmen J. Buxó-Martinez; Jodi A. Psoter; Alexander R. Kerr; Christina M. Lane; Vincent J. Scaringi; Augusto Elias (Journal of Cancer Education, 2015)

Early medieval farming and food production: a review of the archaeobotanical evidence from archaeological excavations in Ireland - Meriel McClatchie; Finbar McCormick; Thomas R. Kerr; Aidan O’Sullivan (Vegetation History and Archaeobotany, 2015)

Assessment of the representation of Antarctic Bottom Water properties in the ECCO2 reanalysis - M. Azaneu; R. Kerr; M. M. Mata (Ocean Science, 2014)
We analyzed the ability of the Estimating the Circulation and Climate of the Ocean – Phase II (ECCO2) reanalysis to represent the hydrographic properties and variability of Antarctic Bottom Water (AABW) in the Southern Ocean. We used a 20-year (1992–2011) observational database to perform comparisons of hydrographic properties and reanalysis output for the same time period. Four case studies based on current meter data and the AABW volume transport estimates previously reported in the literature were also evaluated. The opening and maintenance of an oceanic polynya in the Weddell Sea sector is observed after 2004 in the reanalysis product. Moreover, intense deep water production due to deep convection occurs, which leads to a scenario in which the Weddell Sea is flooded with AABW. For this reason, our analyses focused on the period that was identified as more reliable (1992–2004). The main Southern Ocean oceanographic features, as well as the characteristic shape of the regional potential temperature–salinity (θ–S) diagrams, are coincident with observations. However, the reanalysis output produces surface waters that are generally denser than observations due to the reproduction of waters that are generally saltier than expected, which probably resulted from the strong seasonality of sea ice concentrations. Bottom waters are warmer and less dense, while intermediate waters are statistically closest to the observations. The differences in bottom water properties are partially due to the inability of the reanalysis to properly reproduce the formation and export of dense waters from the shelf and the consequent absence of the densest AABW variety for most of the analyzed period. Despite differences in the absolute values, the upper AABW limit (γn ≥ 28.27 kg m−3) and AABW occupied area estimates are coincident with the observations in the World Ocean Circulation Experiment (WOCE) repeat sections SR2 and SR4. Moreover, the AABW volume export and current velocity variability are correlated with the observed time series in the most important region of dense water export (i.e., the Weddell Sea). Despite the consistency in terms of variability, the absolute volume transport and velocity estimates are underrepresented in all cases.

Assessment of the structure and variability of Weddell Sea water masses in distinct ocean reanalysis products - T. S. Dotto; R. Kerr; M. M. Mata; M. Azaneu; I. Wainer; E. Fahrbach; G. Rohardt (Ocean Science, 2014)
We assessed and evaluated the performance of five ocean reanalysis products in reproducing essential hydrographic properties and their associated temporal variability for the Weddell Sea, Antarctica. The products used in this assessment were ECMWF ORAS4 (European Centre for Medium-Range Weather Forecasts Ocean Reanalysis System 4), CFSR (Climate Forecast System Reanalysis), MyOcean UR025.4 (University of Reading), ECCO2 (Estimating the Circulation and Climate of the Ocean, Phase II) and SODA (Simple Ocean Data Assimilation). The present study focuses on the Weddell Sea deep layer, which is composed of the following three main water masses: Warm Deep Water (WDW), Weddell Sea Deep Water (WSDW) and Weddell Sea Bottom Water (WSBW). The MyOcean UR025.4 product provided the most accurate representation of the structure and thermohaline properties of the Weddell Sea water masses when compared with observations. All the ocean reanalysis products analyzed exhibited limited capabilities in representing the surface water masses in the Weddell Sea. The CFSR and ECCO2 products were not able to represent deep water masses with a neutral density ≥ 28.40 kg m−3, which was considered the WSBW's upper limit throughout the simulation period. The expected WDW warming was only reproduced by the SODA product, whereas the ECCO2 product was able to represent the trends in the WSDW's hydrographic properties. All the assessed ocean reanalyses were able to represent the decrease in the WSBW's density, except the SODA product in the inner Weddell Sea. Improvements in parameterization may have as much impact on the reanalyses assessed as improvements in horizontal resolution primarily because the Southern Ocean lacks in situ data, and the data that are currently available are summer-biased. The choice of the reanalysis product should be made carefully, taking into account the performance, the parameters of interest, and the type of physical processes to be evaluated.

One hundred new universal exonic markers for birds developed from a genomic pipeline - Kevin C. R. Kerr; Alison Cloutier; Allan J. Baker (Journal of Ornithology, 2014)

Predicting the sensitivity of butterfly phenology to temperature over the past century - Heather M. Kharouba; Sebastien R. Paquette; Jeremy T. Kerr; Mark Vellend (Global Change Biology, 2014)
Studies to date have documented substantial variation among species in the degree to which phenology responds to temperature and shifts over time, but we have a limited understanding of the causes of such variation. Here, we use a spatially and temporally extensive data set (ca. 48 000 observations from across Canada) to evaluate the utility of museum collection records in detecting broad‐scale phenology‐temperature relationships and to test for systematic differences in the sensitivity of phenology to temperature (days °C −1 ) of Canadian butterfly species according to relevant ecological traits. We showed that the timing of flight season predictably responded to temperature both across space (variation in average temperature from site to site in Canada) and across time (variation from year to year within each individual site). This reveals that collection records, a vastly underexploited resource, can be applied to the quantification of broad‐scale relationships between species' phenology and temperature. The timing of the flight season of earlier fliers and less mobile species was more sensitive to temperature than later fliers and more mobile species, demonstrating that ecological traits can account for some of the interspecific variation in species' phenological sensitivity to temperature. Finally, we found that phenological sensitivity to temperature differed across time and space implying that both dimensions of temperature will be needed to translate species' phenological sensitivity to temperature into accurate predictions of species' future phenological shifts. Given the widespread temperature sensitivity of flight season timing, we can expect long‐term temporal shifts with increased warming [ca. 2.4 days °C −1 (0.18 SE)] for many if not most butterfly species.

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Dosing of adult pigeons with as little as one #9 lead pellet caused severe δ-ALAD depression, suggesting potential adverse effects in wild populations - Jeremy P. Holladay; Mandy Nisanian; Susan Williams; R. Cary Tuckfield; Richard Kerr; Timothy Jarrett; Lawrence Tannenbaum; Steven D. Holladay; Ajay Sharma; Robert M. Gogal (Ecotoxicology, 2012)

Persistent Increase of Blood Lead Level and Suppression of δ-ALAD Activity in Northern Bobwhite Quail Orally Dosed With Even a Single 2-mm Spent Lead Shot - S. D. Holladay; R. Kerr; J. P. Holladay; B. Meldrum; S. M. Williams; R. M. Gogal (Archives of Environmental Contamination and Toxicology, 2012)

On the outflow of dense water from the Weddell and Ross Seas in OCCAM model - R. Kerr; K. J. Heywood; M. M. Mata; C. A. E. Garcia (Ocean Science, 2012)
We describe the seasonal and interannual variability of volume transports in the Weddell and Ross Seas using the 1/12° 20-yr simulation of the OCCAM global ocean general circulation model. The average simulated full-depth cumulative volume transports were 28.5 ± 2.9 Sv (1 Sv ≡ 106 m3 s−1) and 13.4 ± 5.2 Sv, across the main export regions of the Weddell and Ross Seas, respectively. The values of mean outflow of Antarctic Bottom Water (AABW) (defined by neutral density γn ≥ 28.27 kg m−3) from the Weddell and Ross Seas of 10.6 ± 3.1 Sv and 0.5 ± 0.7 Sv, respectively, agree with the range reported in historical observational studies. The export of Weddell Sea dense water in OCCAM is primarily determined by the strength of the Weddell Gyre. Variability in AABW export is predominantly at periods of ~1 yr and 2–4 yr.

Sources and fate of nutrients in a subtropical reservoir - Michele A. Burford; Susanne A. Green; Andrew J. Cook; Suzanne A. Johnson; Jason G. Kerr; Katherine R. O’Brien (Aquatic Sciences, 2012)

DNA barcoding of Scandinavian birds reveals divergent lineages in trans-Atlantic species - Arild Johnsen; Eirik Rindal; Per G. P. Ericson; Dario Zuccon; Kevin C. R. Kerr; Mark Y. Stoeckle; Jan T. Lifjeld (Journal of Ornithology, 2010)

Derivation of Man-1 and Man-2 research grade human embryonic stem cell lines - Maria V. Camarasa; Robbie W. Kerr; Sharon F. Sneddon; Nicola Bates; Lisa Shaw; Rachel A. Oldershaw; Fiona Small; Melissa A. Baxter; Tristan R. Mckay; Daniel R. Brison; Susan J. Kimber (In Vitro Cellular & Developmental Biology - Animal, 2010)

Genetic variation in PARL influences mitochondrial content - Joanne E. Curran; Jeremy B. M. Jowett; Lawrence J. Abraham; Luke A. Diepeveen; Katherine S. Elliott; Thomas D. Dyer; Lyndal J. Kerr-Bayles; Matthew P. Johnson; Anthony G. Comuzzie; Eric K. Moses; Ken R. Walder; Gregory R. Collier; et al. (Human Genetics, 2010)

Stingless Bees: Chemical Differences and Potential Functions in Nannotrigona testaceicornis and Plebeia droryana Males and Workers - Adriana Pianaro; Cristiano Menezes; Warwick Estevam Kerr; Rodrigo B. Singer; Eda Flávia Lotufo R. A. Patricio; Anita J. Marsaioli (Journal of Chemical Ecology, 2009)

Spatial species‐richness gradients across scales: a meta‐analysis - Richard Field; Bradford A. Hawkins; Howard V. Cornell; David J. Currie; J. Alexandre F. Diniz‐Filho; Jean‐François Guégan; Dawn M. Kaufman; Jeremy T. Kerr; Gary G. Mittelbach; Thierry Oberdorff; Eileen M. O’Brien; John R. G. Turner (Journal of Biogeography, 2009)
Aim We surveyed the empirical literature to determine how well six diversity hypotheses account for spatial patterns in species richness across varying scales of grain and extent. Location Worldwide. Methods We identified 393 analyses (‘cases’) in 297 publications meeting our criteria. These criteria included the requirement that more than one diversity hypothesis was tested for its relationship with species richness. We grouped variables representing the hypotheses into the following ‘correlate types’: climate/productivity, environmental heterogeneity, edaphics/nutrients, area, biotic interactions and dispersal/history (colonization limitation or other historical or evolutionary effect). For each case we determined the ‘primary’ variable: the one most strongly correlated with taxon richness. We defined ‘primacy’ as the proportion of cases in which each correlate type was represented by the primary variable, relative to the number of times it was studied. We tested for differences in both primacy and mean coefficient of determination of the primary variable between the hypotheses and between categories of five grouping variables: grain, extent, taxon (animal vs. plant), habitat medium (land vs. water) and insularity (insular vs. connected). Results Climate/productivity had the highest overall primacy, and environmental heterogeneity and dispersal/history had the lowest. Primacy of climate/productivity was much higher in large‐grain and large‐extent studies than at smaller scales. It was also higher on land than in water, and much higher in connected systems than in insular ones. For other hypotheses, differences were less pronounced. Throughout, studies on plants and animals showed similar patterns. Coefficients of determination of the primary variables differed little between hypotheses and across the grouping variables, the strongest effects being low means in the smallest grain class and for edaphics/nutrients variables, and a higher mean for water than for land in connected systems but vice versa in insular systems. We highlight areas of data deficiency. Main conclusions Our results support the notion that climate and productivity play an important role in determining species richness at large scales, particularly for non‐insular, terrestrial habitats. At smaller extents and grain sizes, the primacy of the different types of correlates appears to differ little from null expectation. In our analysis, dispersal/history is rarely the best correlate of species richness, but this may reflect the difficulty of incorporating historical factors into regression models, and the collinearity between past and current climates. Our findings are consistent with the view that climate determines the capacity for species richness. However, its influence is less evident at smaller spatial scales, probably because (1) studies small in extent tend to sample little climatic range, and (2) at large grains some other influences on richness tend to vary mainly within the sampling unit.

Tactile acuity in experienced Tai Chi practitioners: evidence for use dependent plasticity as an effect of sensory-attentional training - Catherine E. Kerr; Jessica R. Shaw; Rachel H. Wasserman; Vanessa W. Chen; Alok Kanojia; Thomas Bayer; John M. Kelley (Experimental Brain Research, 2008)

Diagnosing Mitochondrial DNA Diversity: Applications of a Sentinel Gene Approach - Elizabeth L. Clare; Kevin C. R. Kerr; Taika E. von Königslöw; John J. Wilson; Paul D. N. Hebert (Journal of Molecular Evolution, 2008)

Differential expression of the keratan sulphate proteoglycan, keratocan, during chick corneal embryogenesis - E. Claire Gealy; Briedgeen C. Kerr; Robert D. Young; Debbie Tudor; Anthony J. Hayes; Clare E. Hughes; Bruce Caterson; Andrew J. Quantock; James R. Ralphs (Histochemistry and Cell Biology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Demonstration of 5-HT3 receptor function and expression in the mouse bladder - N. Chetty; I. M. Coupar; R. Chess-Williams; K. P. Kerr (Naunyn-Schmiedeberg's Archives of Pharmacology, 2007)

Phylogeny and classification of Rosaceae - D. Potter; T. Eriksson; R. C. Evans; S. Oh; J. E. E. Smedmark; D. R. Morgan; M. Kerr; K. R. Robertson; M. Arsenault; T. A. Dickinson; C. S. Campbell (Plant Systematics and Evolution, 2007)

1,25-dihydroxyvitamin D3 protects human pancreatic islets against cytokine-induced apoptosis via down-regulation of the fas receptor - R. Riachy; B. Vandewalle; E. Moerman; S. Belaich; B. Lukowiak; V. Gmyr; G. Muharram; J. Kerr Conte; F. Pattou (Apoptosis, 2006)

Angiotensin II blocks memory consolidation through an AT2 receptor-dependent mechanism - Daniel S. Kerr; Lia R. M. Bevilaqua; Juliana S. Bonini; Janine I. Rossato; Cristiano A. Köhler; Jorge H. Medina; Iván Izquierdo; Martín Cammarota (Psychopharmacology, 2005)

Predictions and tests of climate‐based hypotheses of broad‐scale variation in taxonomic richness - David J. Currie; Gary G. Mittelbach; Howard V. Cornell; Richard Field; Jean‐Francois Guégan; Bradford A. Hawkins; Dawn M. Kaufman; Jeremy T. Kerr; Thierry Oberdorff; Eileen O'Brien; J. R. G. Turner (Ecology Letters, 2004)
Broad‐scale variation in taxonomic richness is strongly correlated with climate. Many mechanisms have been hypothesized to explain these patterns; however, testable predictions that would distinguish among them have rarely been derived. Here, we examine several prominent hypotheses for climate–richness relationships, deriving and testing predictions based on their hypothesized mechanisms. The ‘energy–richness hypothesis’ (also called the ‘more individuals hypothesis’) postulates that more productive areas have more individuals and therefore more species. More productive areas do often have more species, but extant data are not consistent with the expected causal relationship from energy to numbers of individuals to numbers of species. We reject the energy–richness hypothesis in its standard form and consider some proposed modifications. The ‘physiological tolerance hypothesis’ postulates that richness varies according to the tolerances of individual species for different sets of climatic conditions. This hypothesis predicts that more combinations of physiological parameters can survive under warm and wet than cold or dry conditions. Data are qualitatively consistent with this prediction, but are inconsistent with the prediction that species should fill climatically suitable areas. Finally, the ‘speciation rate hypothesis’ postulates that speciation rates should vary with climate, due either to faster evolutionary rates or stronger biotic interactions increasing the opportunity for evolutionary diversification in some regions. The biotic interactions mechanism also has the potential to amplify shallower, underlying gradients in richness. Tests of speciation rate hypotheses are few (to date), and their results are mixed.

Characterisation of axon terminals in the rat dorsal horn that are immunoreactive for serotonin 5-HT3A receptor subunits - D. J. Maxwell; R. Kerr; S. Rashid; E. Anderson (Experimental Brain Research, 2003)

Myelinated and unmyelinated primary afferent axons form contacts with cholinergic interneurons in the spinal dorsal horn - M. J. Olave; N. Puri; R. Kerr; D. J. Maxwell (Experimental Brain Research, 2002)

Compound heterozygosity and nonsense mutations in the α1-subunit of the inhibitory glycine receptor in hyperekplexia - Mark I. Rees; Trevor M. Lewis; Behnaz Vafa; Colin Ferrie; Peter Corry; Fransesco Muntoni; Heinz Jungbluth; John B. Stephenson; Mike Kerr; Russell G. Snell; Peter R. Schofield; Michael J. Owen (Human Genetics, 2001)

Bordetella pertussis Infection: Pathogenesis, Diagnosis, Management, and the Role of Protective Immunity - J. R. Kerr; R. C. Matthews (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

In Vitro Synergy Between Ranitidine Bismuth Citrate and Tetracycline or Clarithromycin Against Resistant Strains of Helicobacter pylori - P. D. Midolo; J. R. Lambert; T. G. Kerr; W. Tee (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Semiquantitative Polymerase Chain Reaction Enzyme Immunoassay for the Diagnosis of Pertussis - R. C. Matthews; N. Golbang; W. M. Brück; D. Owen; A. Bailey; V. Weston; J. R. Kerr (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Slant Column Measurements of O3 and NO2 During the NDSC Intercomparison of Zenith-Sky UV-Visible Spectrometers in June 1996 - H. K. Roscoe; P. V. Johnston; M. Van Roozendael; A. Richter; A. Sarkissian; J. Roscoe; K. E. Preston; J-C. Lambert; C. Hermans; W. DeCuyper; S. Dzienus; T. Winterrath; et al. (Journal of Atmospheric Chemistry, 1999)

Asymptotic rates of response from forest tree breeding strategies using best linear unbiased prediction - R. J. Kerr (Theoretical and Applied Genetics, 1998)

Effects in s.e. Queensland during 1967–72 of insects introduced to controlLantana camara - K. L. S. Harley; J. D. Kerr; R. C. Kassulke (BioControl, 1979)